Solid Catalysts for the Upgrading of Renewable Sources - Zaccheria, Federica (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The use of solid catalysts for the upgrade of renewable sources gives the opportunity to combine the two main cores of green chemistry, that is, on the one hand, the set-up of sustainable processes and, on the other, the use of biomass-derived materials. Solid catalysts have taken on a leading role in traditional petrochemical processes and could represent a key tool in new biorefinery-driven technologies.